Pendidikan Anak Perspektif Kosmologi Islam (Kontekstualisasi Pemikiran Sachiko Murata) - Sofia, Fifin (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2021)
In essence, education is a basic human need, because humans are born endowed with various potentials that must be developed as provisions for living life as servants and representatives of Allah on earth. But in fact today, instead of being God's representative, humans create various chaos, both in their relationships with fellow humans—violence, brawl, bullying—and their relationship with the universe—garbage, air pollution, damage to marine ecosystems, water pollution, forest fires and so on. And the bad news is, Indonesia is included in the 5 countries with the most population in the world, so the habits of the Indonesian greatly influence world conditions. It seems that the various bad conditions that occur are the result of human actions who do not have good morals, this shows that the ongoing education system has not been able to lead humans to have the awareness that everything in the universe is related to one another, especially connection with God—or better known as Cosmology, or if it is compared to one body, when one limb is injured then the whole body feels the impact. This study aims to: 1) Know how the Islamic Cosmology Perspective of Sachiko Murata; 2) Knowing the concept of Islamic Cosmological Perspective Child Education in the contextualization of Sachiko Murata's thoughts. The research method used is descriptive qualitative, which has the primary source from Sachiko Murata's book The Tao of Islam, while the data collection technique uses literature study, and the data collected is analyzed using processing, categorization and interpretation. The results of this study are (1) God is viewed in two perspectives (duality), tanzih (incommensurability) and tasybih (likeness). To know God, Murata uses the tasybih approach. Islamic cosmology aims to emphasize tauhid (the oneness of Allah), which is depicted in the form of a triangle, encompassing God, nature and man in every corner, so that there is unity and interrelation between all realities; (2) Child education in the perspective of Islamic cosmology according to Sachiko Murata, building divine awareness that God is not only about Himself who is far from the reach of creatures, but we can see God scattered throughout the horizon and soul.